Fostering a High-Functioning Team in Cancer Care Using the 4R Oncology Model: Assessment in a Large Health System and a Blueprint for Other Institutions. Issue 1 (30th September 2022) - Liu, Raymond; Weldon, Christine B.; Linehan, Elizabeth; Gordon, Nancy; Abbe, Thea; Hennings, Marti; James, Henie; Katzel, Jed; Ng, Chun; Tomita, Megumi; Velotta, Jeffrey B.; Ossowski, Stephanie; et al.
Abstract : PURPOSE: Delivering cancer care by high-functioning multidisciplinary teams promises to address care fragmentation, which threatens care quality, affects patient outcomes, and strains the oncology workforce. We assessed whether the 4R Oncology model for team-based interdependent care delivery and patient self-management affected team functioning in a large community-based health system. METHODS: 4R was deployed at four locations in breast and lung cancers and assessed along four characteristics of high-functioning teams: recognition as a team internally and externally; commitment to an explicit shared goal; enablement of interdependent work to achieve the goal; and engagement in regular reflection to adapt objectives and processes. RESULTS: We formed an internally and externally recognized team of 24 specialties committed to a shared goal of delivering multidisciplinary care at the optimal time and sequence from a patient-centric viewpoint. The team conducted 40 optimizations of interdependent care (22 for breast, seven for lung, and 11 for both cancers) at four points in the care continuum and established an ongoing teamwork adaptation process. Half of the optimizations entailed low effort, while 30% required high level of effort; 78% resulted in improved process efficiency. CONCLUSION: 4R facilitated development of a large high-functioning team and enabled 40 optimizations of interdependent care along the cancer care continuum in a feasible way. 4R may be an effective approach for fostering high-functioning teams, which could contribute to improving viability of the oncology workforce. Our intervention and taxonomy of results serve as a blueprint for other institutions motivated to strengthen teamwork to improve patient-centered care.